Amyloid Arthropathy: A Review. (November 2021) - Diaz-Perez, Julio A.; Conway, Sheila A.; Zuo, Yiqin; Nielsen, Gunnlaugur Petur; Selig, Martin; Rosenberg, Andrew E.
Abstract : Amyloid arthropathy is a joint disease associated with systemic amyloidosis. Herein, we present a model case and review the clinicopathologic features and pathophysiology of this disorder. Amyloid arthropathy results from elevation of serum amyloidogenic proteins and their deposition as aggregates in synovial fluid and articular tissues. The most common proteins are beta-2-microglobulin in the context of long-term hemodialysis therapy and immunoglobulin light chains associated with plasma cell proliferations. We provide a comprehensive update on the pathogenesis, clinical manifestations, and pathologic features of amyloid arthropathy. We provide detailed insights on amyloid protein deposition and aggregation in joints and proper details for diagnosis.